2016
DOI: 10.6061/clinics/2016(03)09
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic versus surgical gastrostomy in patients with benign and malignant diseases: a systematic review and meta-analysis

Abstract: To compare the complications and mortality related to gastrostomy procedures performed using surgical and percutaneous endoscopic gastrostomy techniques, this review covered seven studies. Five of these were retrospective and two were randomized prospective studies. In total, 406 patients were involved, 232 of whom had undergone percutaneous endoscopic gastrostomy and 174 of whom had undergone surgical gastrostomy. The analysis was performed using Review Manager. Risk differences were computed using a fixed-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
0
27
1
6
Order By: Relevance
“…The mean operation time is relatively longer for laparoscopic gastrostomy and relatively shorter for PEG in literature (6,9,23). The mean operation time in our study was 34 ± 12.8 minutes and it was relatively very short considering these risky patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The mean operation time is relatively longer for laparoscopic gastrostomy and relatively shorter for PEG in literature (6,9,23). The mean operation time in our study was 34 ± 12.8 minutes and it was relatively very short considering these risky patients.…”
Section: Discussionmentioning
confidence: 51%
“…Gastrostomy can be performed by means of endoscopic, radiologic or surgical methods (4). Percutaneous endoscopic gastrostomy (PEG) is a simple, cheap and of a very low complication risk procedure, which does not need general anaesthesia (1,5,6). Surgical gastrostomy (SG) is an invasive procedure and frequently necessitates general anaesthesia (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As complicações em gastrostomia são classificadas, de acordo com a gravidade, em sistêmicas ou menores. Entre as complicações menores destacam-se: deslocamento ou saída acidental do cateter, vazamento de conteúdo gástrico, dermatite, granuloma e infecção periestomia, as quais demandam tratamento conservador (2,16) . No presente estudo foram encontradas apenas complicações de menor gravidade ficando evidente a baixa taxa de complicações pelo uso de gastrostomia em crianças.…”
Section: Discussionunclassified
“…Open gastrostomy involves a gastric incision to place the tube. Studies comparing SG with PEG have shown no differences in morbidity and mortality rates; nevertheless, PEG is less expensive and is easier and faster to perform [49]. SG is commonly reserved for patients who will undergo another surgical procedure or in a setting in which PEG and RIG are contraindicated or not locally available [49,50].…”
Section: Surgical Gastrostomymentioning
confidence: 99%